Penggunaan Media Gambar Seri untuk Meningkatkan Kemampuan Menulis dan Membaca Mata Pelajaran Tematik - Susbandiyah; Miftahudin (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
Given the importance of reading and writing in the learning process at school, the teacher plays an essential role in motivating students to like reading and writing. Learning media helps teachers manage the teaching process and use class time well. The type of research used is classroom action research. The result stated that the serial picture media greatly influenced the students' writing and reading abilities. Students' writing and reading skills increased significantly, with complete writing ability reaching 93% and full writing ability by 89%.